The Dynamic Effects of Commodity Prices on Fiscal Performance in Latin America - Medina, Leandro (IMF Working Papers; Working Paper, 2010)
The recent boom and bust in commodity prices has raised concerns about the impact of volatile commodity prices on Latin American countries' fiscal positions. Using a novel quarterly data set-which includes unique country-specific commodity price indices and a comprehensive measure of public expenditures-this paper analyzes the dynamic effects of commodity price fluctuations on fiscal revenues and expenditures for eight commodity-exporting Latin American countries. The results indicate that Latin American countries' fiscal positions react strongly to shocks to commodity prices, yet there are marked differences across countries. Fiscal variables in Venezuela display the highest sensitivity to commodity price shocks, with expenditures reacting significantly more than revenues. At the other end of the spectrum, in Chile expenditure reacts very little to commodity price fluctuations, and the dynamic responses of its fiscal indicators are very similar to those seen in high-income commodity-exporting countries. This distinct behavior across countries may relate to institutional arrangements, which in some cases include the efficient application of fiscal rules amid political commitment and high standards of transparency.